Boreal Shield Watersheds: Lake Trout Ecosystems in a Changing Environment - Gunn, John M (CRC Press, 2009)
Boreal Shield Watersheds: Lake Trout Ecosystems in a Changing Environment brings together the work of a renowned international group of scientists who specialize in aquatic science and environmental management. They explore the functioning of Boreal Shield ecosystems, focusing on the lake trout, the classic coldwater species of northern glaciated lakes, using it as an indicator of environmental change and as a model to measure the effectiveness of management actions.